HUBUNGAN KEGIATAN USAHA KESEHATAN SEKOLAH (UKS) DENGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) - Linda Novial Dwi (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
Background: School health efforts (UKS) is an integrated program in order to improve the quality of education and learning achievement of learners which is reflected in the life of clean and healthy life behavior, creating a healthy environment, enabling harmonious growth and optimal development. A healthy school environment is certainly very supportive in the achievement of educational goals, the implementation of three main programs of UKS namely health education, health services and environmental coaching. Implementation of clean and healthy living behavior (PHBS) will be easier if taught since the child was at school age. Objective: To know the relationship of health business activity (UKS) with clean and healthy life behavior (PHBS). Method: The type of research used is Descriptive Correlation, with Cross Sectional research design. The sample size is 56 students using Probability Sampling with Stratified random sampling technique. In this research the statistical test used is the fisher exact test test. Result: From correlation analysis of school health business activity (UKS) with clean and healthy life behavior (PHBS), P value = 0,000 <α = (0,05) so that Ha is accepted which means there is relationship between school health business activity (UKS) With the behavior of clean and healthy life (PHBS) in SMP Negeri 11 Samarinda. Conclusion: School health business activity (UKS) is related to clean and healthy life behavior (PHBS) therefore schools are able to improve PHBS through UKS activities so that the health status of all school residents will be optimal.